2021
DOI: 10.1111/ajad.13247
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing autistic traits in treatment‐seeking young adults with substance use disorders

Abstract: Background and Objectives: Recent work highlights an increase in the overlap of autism spectrum disorder (ASD) and substance use disorder (SUD). Little is known about the presence of ASD symptoms in SUD-treatment-seeking populations. Methods:The informant-rated Social Responsiveness Scale-2 (SRS-2) was completed at intake to an outpatient SUD clinic for youth aged 16-26 (N = 69). Comparisons were made between those with elevated SRS-2 scores on demographic, psychiatric, and substance use variables.Results: Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The co-occurrence of substance use and psychopathology (dual diagnosis) can be explained by shared risk factors such as socioeconomic status and personality traits [30][31][32]. Many people with SUDs show psychiatric comorbidity, personality, mood, and anxiety disorders [12,[30][31][32][33], especially in cases of poly-drug use, where eating disorders, psychotic symptoms, schizophrenia [2], and PTSD (Post-Traumatic Stress Disorder) [4,34] can also be found; in some cases, the dual diagnosis of SUD and ASD (Autism Spectrum Disorder) is also found [35].…”
Section: Complex Entanglement: Substance Use Disorder; Personality; A...mentioning
confidence: 99%
See 3 more Smart Citations
“…The co-occurrence of substance use and psychopathology (dual diagnosis) can be explained by shared risk factors such as socioeconomic status and personality traits [30][31][32]. Many people with SUDs show psychiatric comorbidity, personality, mood, and anxiety disorders [12,[30][31][32][33], especially in cases of poly-drug use, where eating disorders, psychotic symptoms, schizophrenia [2], and PTSD (Post-Traumatic Stress Disorder) [4,34] can also be found; in some cases, the dual diagnosis of SUD and ASD (Autism Spectrum Disorder) is also found [35].…”
Section: Complex Entanglement: Substance Use Disorder; Personality; A...mentioning
confidence: 99%
“…SUD and Autism Spectrum Disorder (ASD) are often found in comorbidity with each other, resulting in a dual diagnosis; in most of these cases, people use substances as a means to manage high levels of anxiety, stress, and social difficulties, including perceived social rejection [35]. The cause of this phenomenon seems mainly neurobiological, although its interaction with psychological aspects will be explored in depth in another paragraph.…”
Section: Sud and Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…This large variability likely reflects the varied samples and methodologies used assessing SUD. Despite the lack of definitive data on substance use in people with ASD, it has been recently reported that 20% of young people aged 16-26 years old presenting for primary SUD treatment manifest prominent ASD traits as assessed by parental report on the social responsiveness scale–second edition (SRS-2) [ 16 ]. Althougth the SRS-2 is not an autism diagnostic tool, the results of this study suggest that when present, elevated autism traits by parental report appear to signal a distinct subset of clients (see McKowen et al [ 16 ] for additional information).…”
Section: Introductionmentioning
confidence: 99%